The Influence of the Plant Growth Regulator Maleic Hydrazide on Egyptian Broomrape Early Developmental Stages and Its Control Efficacy in Tomato under Greenhouse and Field Conditions - Venezian, Ariel; Dor, Evgenia; Achdari, Guy; Plakhine, Dina; Smirnov, Evgeny; Hershenhorn, Joseph (Frontiers in Plant Science, 2017)
Broomrapes (Phelipanche spp. and Orobanche spp.) are holoparasitic plants that cause tremendous losses of agricultural crops worldwide. Broomrape control is extremely difficult and only amino acid biosynthesis-inhibiting herbicides present an acceptable control level. It is expected that broomrape resistance to these herbicides is not long in coming. Our objective was to develop a broomrape control system in tomato (Solanum lycopersicum L.) based on the plant-growth regulator maleic hydrazide (MH). Petri-dish and polyethylene-bag system experiments revealed that MH has a slight inhibitory effect on Phelipanche aegyptiaca seed germination but is a potent inhibitor of the first stages of parasitism, namely attachment and the tubercle stage. MH phytotoxicity toward tomato and its P. aegyptiaca-control efficacy were tested in greenhouse experiments. MH was applied at 25, 50, 75, 150, 300 and 600 g a.i. ha-1 to tomato foliage grown in P. aegyptiaca-infested soil at 200 growing degree days (GDD) and again at 400 GDD. The treatments had no influence on tomato foliage or root dry weight. The total number of P. aegyptiaca attachments counted on the roots of the treated plants was significantly lower at 75 g a.i. ha-1 and also at higher MH rates. Phelipanche aegyptiaca biomass was close to zero at rates of 150, 300 and 600 g a.i. ha-1 MH. Field experiments were conducted to optimize the rate, timing and number of MH applications. Two application sequences gave superior results, both with five split applications applied at 100, 200, 400, 700 and 1000 GDD: (a) constant rate of 400 g a.i. ha-1; (b) first two applications at 270 g a.i. ha-1 and the next three applications at 540 g a.i. ha-1. Based on the results of this study, MH was registered for use in Israel in 2013 with the specified protocol and today, it is widely used by most Israeli tomato growers.